Legal Complexity in Dealing with Cyber Crime in Indonesia - Dijan Widijowati (Research Horizon, 2022)
The development of criminal activities alongside technological advancements demands the evolution of law enforcement instruments to remain relevant and effective. The rampant prevalence of cybercrime in contemporary society has introduced legal complexities in its mitigation. Cybercrimes have evolved and become increasingly intricate. To address these challenges, new legal regulations with a technological approach are necessary. Indonesia has implemented such an instrument, namely the Electronic Information and Transactions Law (UU ITE). However, despite its implementation to combat cybercrime, several complexities persist. This research adopts a normative approach with a descriptive model. It aims to analyze the complexities associated with the implementation of the UU ITE in addressing cybercrime in Indonesia. In the face of rapid technological advancements, cybercrimes have become more intricate and require appropriate legal approaches. The research endeavors to contribute to the understanding and development of the implementation of the UU ITE in combating cybercrime in Indonesia. The findings of this research are expected to serve as a foundation for enhancing the effectiveness and efficiency of cybercrime management, thereby safeguarding society's digital activities. In conclusion, the growing threat of cybercrime necessitates continuous adaptation and improvement of law enforcement instruments. The research seeks to shed light on the complexities of implementing the UU ITE in Indonesia and provide valuable insights for the enhancement of its efficacy. By doing so, it aspires to contribute to the protection of individuals and communities in the digital realm.